2015
DOI: 10.2147/rrb.s62507
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in breast cancer

Abstract: Abstract:The reprogramming of the mitochondria of cancer cells is essential for their growth. However, such reprogramming leads to the increased formation of reactive oxygen species, which can lead to damage to the organelle. This review summarizes the mechanisms that protect the mitochondrial network against oxidative stress. Further, since several transcription factors have now been linked to the mitochondrial unfolded protein response (UPR mt ) and regulate the expression of one or more genes involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…It is well known that (mtDNA) has a mutation rate several times higher than nuclear DNA [15], due to its limited repair mechanisms, lack of protective histones and its close proximity to the electron transport chain, which continuously generates free radicals [16]; in addition, mtDNA is organized in an economic pattern with its genes lacking introns [17]. It was in 1956, when Otto Warburg observed that cancers ferment glucose in the presence of oxygen, proposing that abnormalities in mitochondrial respiration may be responsible for cancer production [16, 18, and 19]. Now it’s well-established that changes in the biochemical processes that accompany the process of carcinogenesis as the aerobic glycolesis do not impair mitochondrial function but are rather essential for cancer cell viability [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that (mtDNA) has a mutation rate several times higher than nuclear DNA [15], due to its limited repair mechanisms, lack of protective histones and its close proximity to the electron transport chain, which continuously generates free radicals [16]; in addition, mtDNA is organized in an economic pattern with its genes lacking introns [17]. It was in 1956, when Otto Warburg observed that cancers ferment glucose in the presence of oxygen, proposing that abnormalities in mitochondrial respiration may be responsible for cancer production [16, 18, and 19]. Now it’s well-established that changes in the biochemical processes that accompany the process of carcinogenesis as the aerobic glycolesis do not impair mitochondrial function but are rather essential for cancer cell viability [15].…”
Section: Introductionmentioning
confidence: 99%